A simulated annealing algorithm for the robust decomposition of temporal horizons in production planning problems (2007)
The problem of robust decomposition of temporal horizons in production planning was ﬁrst introduced by Torres [1]. Later, in [2], Torres suggests to start with an integer solution found by dynamic programming, and then to use a simulated annealing algorithm to improve it. According to [2], more needs to be known about the impact of the control parameters in the simulated annealing algorithm, and their sensitivity with respect to the quality of the solutions. In this work we develop this idea and analyze in depth the ability of the simulated annealing algorithm to improve the initial solution. As a result of the computational experiments conducted, we determined that the cooling scheme and the cooling rate have signiﬁcant eﬀect on the quality of the ﬁnal solution. It was also established that the solution found depends strongly on the characteristics of the operations plan, ﬁnding better solutions for plans with shorter temporal horizons.